Strengths and Weaknesses of Facebook and Twitter as Educational Environments in the Context of Structures for Informatics Course at the National University of Costa Rica - Vílchez-Quesada, Enrique (2016)
During the first half of 2013 a set of teaching and learning experiences is implemented in the course Discrete Structures for Computer using as a primary means of social interaction networks Facebook and Twitter. This was part of the responsibilities associated with a research project on teaching enrolled in the School of Computing at the National University of Costa Rica (UNA). The objective of this methodology implementation was to determine the impact of the use of the aforementioned social networks to develop teaching and learning in a formal educational context. The pedagogical proposal was based on the implementation of eight teaching strategies designed by the author of this document. At the end of the intervention process a series of research tools to the participating student population were given, and some strengths and weaknesses of social networks Facebook and Twitter as educational environments were obtained.